2000
DOI: 10.1002/1097-0177(2000)9999:9999<::aid-dvdy1015>3.3.co;2-6
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal‐specific expression of Fgd1 during bone formation and skeletal defects in faciogenital dysplasia (FGDY; Aarskog syndrome)

Abstract: FGD1 encodes a guanine nucleotide exchange factor (GEF) that specifically activates the Rho GTPase Cdc42; FGD1 mutations result in Faciogenital Dysplasia (FGDY, Aarskog syndrome), an X-linked developmental disorder that adversely affects the formation of multiple skeletal structures. To further define the role of FGD1 in skeletal development, we examined its expression in developing mouse embryos and correlated this pattern with FGDY skeletal defects. In this study, we show that Fgd1, the mouse FGD1 ortholog, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
38
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(40 citation statements)
references
References 23 publications
2
38
0
Order By: Relevance
“…On the basis of its subcellular localization, FGD1 was suggested to participate in both membrane transport and actin remodeling (Estrada et al, 2001), two processes that have fundamental roles in tissue biogenesis. Moreover, use of in situ hybridization has shown that FGD1 mRNA is up-regulated during bone development (and to a lesser extend in other connective tissues), together with a number of proteins that are involved in bone morphogenesis (Gorski et al, 2000). Here, we have shown that FGD1 is required for effective transport of cargo proteins from the Golgi complex to the plasma membrane in general, whereas in osteoblasts it regulates the secretion of PC-I, osteocalcin, osteonectin, and osteopontin.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…On the basis of its subcellular localization, FGD1 was suggested to participate in both membrane transport and actin remodeling (Estrada et al, 2001), two processes that have fundamental roles in tissue biogenesis. Moreover, use of in situ hybridization has shown that FGD1 mRNA is up-regulated during bone development (and to a lesser extend in other connective tissues), together with a number of proteins that are involved in bone morphogenesis (Gorski et al, 2000). Here, we have shown that FGD1 is required for effective transport of cargo proteins from the Golgi complex to the plasma membrane in general, whereas in osteoblasts it regulates the secretion of PC-I, osteocalcin, osteonectin, and osteopontin.…”
Section: Discussionmentioning
confidence: 99%
“…Apparently this can be explained by a consideration of the expression profile of FGD1: although FGD1 can be detected by Western blotting in cell lines of non-bone origin (e.g., HeLa cells), in situ some tissues (and bone especially) show more FGD1 expression than others (Gorski et al, 2000). FGDY manifestations in the heart and in the urogenital system have also been reported (Scott, 1971) and would correspond to the moderate FGD1 expression seen in these tissues during development (Pasteris et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations